Nutritional Status in Children with Un-Operated Congenital Heart Disease: An Egyptian Center Experience - Hassan, Basheir A.; Albanna, Ehab A.; Morsy, Saed M.; Siam, Ahmed G.; Al Shafie, Mona M.; Elsaadany, Hosam F.; Sherbiny, Hanan S.; Shehab, Mohamed; Grollmuss, Oswin (Frontiers in Pediatrics, 2015)
Background: Malnutrition is a common cause of morbidity and mortality in children with congenital heart disease (CHD).This study aimed to identify prevalence and predictors of malnutrition in Egyptian children with symptomatic CHD. Methods: This case-control study included 100 children with symptomatic CHD (76 acyanotic and 24 cyanotic) and 100 age and sex-matched healthy children as a control group. Clinical Evaluation and Laboratory Assessment of Nutritional Status were done. Anthropometric measurements were recorded and Z scores for weight for age (WAZ), weight for height (WHZ) and height for age (HAZ) were calculated. Malnutrition was defined as weight, height and weight/ height z-score ≤ –2. Results: The overall prevalence of malnutrition was 84.0% in patients with CHD and 20% in controls. Severe malnutrition was diagnosed in 71.4% of cases. All anthropometric measurements and levels of biochemical markers of nutritional state were significantly lower in the patients group compared to controls. In patients with acyanotic CHD, stunting was proportionately higher (57.89%) than in cyanotic CHD, while wasting was predominant (45.83%) in the latter. Malnutrition correlated significantly with low hemoglobin level, low arterial oxygen saturation, heart failure, pulmonary hypertension and poor dietary history. Conclusion: Malnutrition is a very common problem in children with symptomatic CHD and predicted by the presence of low hemoglobin level, low arterial oxygen saturation, heart failure, poor dietary history and pulmonary hypertension.